Development of E-Learning Video Using a Contextual Approach to Distance Learning Static Fluid Discussion - Vina Serevina; I Made Astra; Feren Vini Danoza (Asian Journal of Science Education, 2021)
This research is motivated by the state of distance learning due to the pandemic which has drastically changed teaching and learning activities, so learning media that is suitable for the existing situation is needed. This study aims to develop and produce an e-learning video using a contextual approach to distance learning static fluid discussion. This study uses the Research and Development (RD) method which refers to a 4D model. The instrument in this study was a questionnaire using the Likert scale. This e-learning video has passed the validation test with the proportion of material experts 93.8% and media experts 72%. Video trials were conducted on 35 students of class XI MIPA and 1 physics teacher at SMA Negeri 2 Tangerang with a proportion of 100% according to the teacher and 91% according to the student. This research has improved in terms of material but needs further development in terms of media and science process skills. Based on these results, obtained data that e-learning video that has been developed using a contextual approach to distance learning static fluid discussion is a suitable media for learning physics.